Antimicrobial activity of the essential oil of Phlomis bracteosa - Joshi, RK; Pande, Veena; Thakuri, BC (Scientific World, 2011)
The essential oil was isolated from the aerial parts of Phlomis bracteosa Royle ex Benth., a hairy erect herb. The leaves and flowers of this species are used as carminative, stimulant and locally known as ‘Ballikotu, Calba, Salba’ in Turkish traditional medicine. The antimicrobial activity of Phlomis bracteosa was studied using well diffusion method. The activity was tested against human pathogenic bacteria and fungi at different concentrations (0.25 μg/ml, 0.125 μg/ml and 0.062 μg/ml) of the essential oil. Keywords: Phlomis bracteosa; Lamiaceae; Antimicrobial activity DOI: http://dx.doi.org/10.3126/sw.v9i9.5521 SW 2011; 9(9): 63-65